Age-related trends in cannabis use in Australia. Findings from a series of large nationally representative surveys. (December 2021) - Chan, Gary; Chiu, Vivian; Sun, Tianze; Connor, Jason P.; Hall, Wayne D.; Leung, Janni
Highlights: There is a diverging trend of cannabis use between the younger and older age groups. Prevalence of abstinence among the 55–74 year-olds decreased from 99% to 95%. Prevalence of abstinence among the 14–17 year-olds increased from 79% to 92%. Abstract: Aim: We examine age-related trends in past-year cannabis use in a series of nationally representative surveys in Australia. Methods: We analysed data from the largest nationally representative survey in Australia collected between 2001 and 2019 (National Drug Strategy Household Survey [NDSHS]; N = 157, 151). Prevalence of past-year daily/occasional (non-daily)/non-use of cannabis use were estimated using weighted multinomial logistic regression and predicted marginal probabilities. Difference-in-difference analysis was used to examine if trends of cannabis use across age groups were different. Results: The youngest age group (14–17 s) witnessed the largest increase in past-year abstinence rate from 79% to 92% from 2001 to 2019 ( p  < .003); the increase in abstinent rate among the 18–24 and 25–39 were relatively moderate (from 68 to 76% and from 81% to 84% respectively; p  < .003). The abstinent rate among the 40–54 s and 55–74 s decreased significantly from 93% to 90% and from 99% to 95% respectively ( p  < .003). There were similar diverging trends in occasional and daily cannabis use, with decreases in both patterns of use observed among the younger age group (14–17 s and 18–25 s) but increases among the older age group (40–54 s and 55–74 s). Conclusion: There is a diverging trend in cannabis use among younger and older age groups in Australia between 2001 and 2019. Cannabis use substantially decreased among the youngest age group (14–17 s) but modestly increased among older people (55–74 s).